FACTORS ASSOCIATED WITH H. PYLORI INFECTION AMONG PATIENTS ATTENDING OUTPATIENT DEPARTMENT AT OUR LADY OF CONSOLATA, KISUBI HOSPITAL. A CROSS-SECTIONAL STUDY. - Tusingwire, Catherine; Lujjimbirwa, Fortunate (Student’s Journal of Health Research Africa, 2024)
Background Helicobacter pylori (H. pylori) is a Gram-negative spiral bacterium that has long been recognized for its ability to chronically colonize the gastric mucosa and intestine, causing gastritis duodenal ulcers, and gastric carcinoma. This study aimed to assess factors associated with H. pylori infection among patients attending the outpatient department at Our Lady of Consolata, Kisubi Hospital. Methodology A descriptive cross-sectional study was employed, and a total of 115 study participants were enrolled using a simple random sampling technique. A semi-structured questionnaire was used to collect information on demographic data, family structure, socio-economic status, level of education, type of drinking water, and hygienic habits of the study participants, stool samples collected from the study participants were tested for the presence of H. pylori using H. pylori antigen test strips. Results 68(59.1%) of the respondents were married, the most frequent age was that of below 20 years 27.8%, not washing hands 43(55.1%) with OR=2.6(1.12-5.81), p value= 0.0247 was associated with H. pylori infection. H. pylori was exhibited more in married participants at a rate of 51.3%, OR=0.3(0.14-0.81), p=0.0149) and in single people at a rate of 48.7%, OR=2.9(1.24-7.07). Taking unboiled water by the participants increased the chances of them being positive for H. pylori, as this was seen in participants who took unboiled water, these exhibited 64.1%, OR=5.5(2.29-13.42), p=0.0001 and Participants that lived more than 4 people in a household exhibited a high rate of 59.0% OR=0.6(0.26-1.40). Conclusion Improper hand washing and drinking of un-boiled water were the most predisposing factors associated with H. pylori infection. Recommendation Village health team with local leaders should emphasize hand washing after visiting the latrine and before eating found this will reduce the transmission of H. pylori.